POTENSI BAKTERI ASAM LAKTAT DALAM MENGHASILKAN BAKTERIOSIN SEBAGAI ANTIMIKROBA DAN PENGUKURAN BERAT MOLEKULNYA DENGAN SDS-PAGE DARI ISOLAT FERMENTASI KAKAO - Urnemi -; Sumaryati Syukur; Endang Purwati; Sanusi Ibrahim; Jamsari - (Jurnal Riset Kimia, 2011)
ABSTRACTLactic acid bacteria (LAB) were isolated from cocoa beans fermentation Forestero variety from West Sumatera, that were eleven isolates. The isolates were tested to antimicrobial activity against pathogenic bacteria E.coli NBRC 14237, Staphylococcus aureus NBRC 13276, Bacillus subtilis BTCCB 612, listeria m. dan S. Typhii.Results the research showed that, isolates had inhibition zone to pathogenic bacteria, that were 7 mm till 12 mm at 48 hours observation. R2.4 isolate was most potential to inhibition zones growth pathogenic bacteria, That was 11mm till 12 mm to five pathogens. R2.4 isolates was the highest to against pathogenic bacteria (Bacillus subtilis BTCCB, Listeria monocytogenesis and Staphylococcus aureus NBRC) had inhibition zones, that was 12. mm till 48 hours. Listeria monocytogenesis had been known as pest bacterium of food born, so that R2.4 isolate can be used as food biopreservative. Crude of R2.4 isolate molecular weight was 10 kDa by SDS-PAGE.  Key words: Lactic acid bacteria, antimicrobial activity, SDS-PAGE, cocoa fermentation  and food biopreservative